Leading in a VUCA Environment: U is for Uncertainty - and Kail, Col Eric G. (Harvard Business Review, 2010)
This post is part of an HBR Spotlight examining leadership lessons from the military. It’s the second in a series on the four aspects of VUCA, a framework used by the U.S. military to describe the environment in terms of volatility, uncertainty, complexity, and ambiguity. The frenetic pace of our environment, brought on by volatility, […]
Keywords: Leadership